Deletion of the diabetes candidate gene Slc16a13 in mice attenuates diet-induced ectopic lipid accumulation and insulin resistance - Tina Schumann (Nature Portfolio, 2021)
Schumann et al. demonstrate that the loss of a lactate transporter Slc16a13 increases mitochondrial respiration in the liver, which reduces hepatic lipid accumulation while increasing hepatic insulin sensitivity in mice fed a high-fat diet. This study suggests SLC16A13 as a potential target for the treatment of type 2 diabetes and non-alcoholic fatty liver disease.